Investigating Iraqi EFL University Students' Understanding of Assertive Verbs with Reference to Assertion Acts in Political Context: A PragmaSyntactic Analysis - Mohamed Jaber Alzaghir, Alaa; Malik Mnaathar, Inas (International Journal of Psychosocial Rehabilitation, 2020)
This paper scrutinizes Iraqi EFL university students’ ability in understanding and recognizing the expressions of assertion in political assertive situations. The study investigates the use of assertive verbs in assertive situation(s) in English sentences as used by Iraqi EFL university students with reference to a speech act of assertion. In pursuing this aim, the investigated data has been captured from undergraduate Iraqi EFL college fourth-year students of Thi-Qar University, Colleges of Education and Arts, Department of English. It encompasses 50 Iraqi EFL university students wherein Arabic is their mother tongue. The data were divided into two groups, and each group consists of 25 students (i.e., participants) to touch briefly on the speech act of assertion.The study takes into consideration the gender of the participants while enforcing assertion. Accordingly, the participants are asked to give careful attention to the gender variety and its influence on the execution of the speech act of assertion in assertive situation(s). The instrument of data collection is Discourse Completion Tasks (DCTs). It consists of 8 different written situations. Because the DCTs can be translated into any language, the results, findings, and outcomes are shown in percentages and then visualized in tables and figures. Based on an in-depth reading of the empirical evidence(s) from our qualitative and quantitative analysis, the study mainly found that assertion can be recognized and expressed in different sentence types with different degrees in political situations for a persuasive end. (For more results and findings, see section 4).